The development of GADD45α luciferase reporter assays in human cells for assessing the genotoxicity of environmental pollutants. (February 2015) - Xin, Lili; Wang, Jianshu; Wu, Yanhu; Guo, Sifan
Abstract Objectives: In order to assess the potential carcinogenic and genotoxic responses induced by environmental pollutants, genotoxicity test systems based on a GADD45α promoter-driven luciferase reporter in human A549 and HepG2 cells were established. Materials and methods: Four different types of environmental toxicants including DNA alkylating agents, precarcinogenic agents, DNA cross-linking agents and non-carcinogenic agents, and three environmental samples collected from a coke oven plant were used to evaluate the test systems. After treated with the tested agents and environmental samples for 12 h, the cell viabilities and luciferase activities of the luciferase reporter cells were determined, respectively. Results: Methyl methanesulfonate, benzo[a]pyrene, formaldehyde and the extractable organic matter (EOM) from coke oven emissions in ambient air generally produced significant induction of relative luciferase activity in a similar dose-dependent manner in A549- and HepG2-luciferase cells. No significant increases in relative luciferase activity were observed in pyrene-treated A549- or HepG2-luciferase cells. Significant increase in relative luciferase activity was already evident after 2.5 µM benzo[a]pyrene, 5 µM formaldehyde, 0.006 µg/L bottom-EOM, 0.10 µg/L side-EOM or 0.06 µg/L top-EOM, where no cytotoxic damage was observed. Compared with the A549-luciferase cells, the tested pollutants produced higher induction of relative luciferase activity in HepG2-luciferase cells. Discussion and conclusion: Therefore, the new genotoxicity test systems can detect different types of genotoxic agents and low concentrations of environmental samples. The luciferase reporter cells, especially the HepG2-luciferase cells, could provide a valuable tool for rapid screening of the genotoxic damage of environmental pollutants and their complex mixtures.